Carbon Dioxide versus Air Insufflation in Gastric Endoscopic Submucosal Dissection: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ramkaji Baniya (Clinical Endoscopy, 2017)
Background/Aims Endoscopic submucosal dissection (ESD) with air insufflation is commonly used for the staging and treatment of early gastric carcinoma. However, carbon dioxide (CO2) use has been shown to cause less post-procedural pain and fewer adverse events. The objective of this study was to compare the post-procedural pain and adverse events associated with CO2 and air insufflation in ESD. Methods A systematic search was conducted for randomized control trials (RCTs) comparing the two approaches in ESD. The Mantel-Haenszel method was used to analyze the data. The mean difference (MD) and odds ratio (OR) were used for continuous and categorical variables, respectively. Results Four RCTs with a total of 391 patients who underwent ESD were included in our meta-analysis. The difference in maximal post-procedural pain between the two groups was statistically significant (MD, -7.41; 95% confidence interval [CI], -13.6 – -1.21; p=0.020). However, no significant differences were found in the length of procedure, end-tidal CO2, rate of perforation, and postprocedural hemorrhage between the two groups. The incidence of overall adverse events was significantly lower in the CO2 group (OR, 0.51; CI, 0.32–0.84; p=0.007). Conclusions: CO2 insufflation in gastric ESD is associated with less post-operative pain and discomfort, and a lower risk of overall adverse events compared with air insufflation.